The immune response of chickens vaccinated against Newcastle disease with live Newcastle disease V4 vaccine - Ibrahim, Abdul Latif; Ungku Mohsin, Mohd. Ungku Chulan; Babjee, Ahmad Mustaffa (Australian Veterinary Association, 1980)
Vaccination of chickens with the commercial Newcastle Disease (ND) V4 vaccine at 21 days old or at 21 and 35 days old, stimulated satisfactory and persistent HI antibody levels. The vaccinated chickens were immune when challenged at 49 days old or 77 days old with the virulent strain of NDV administered intramuscularly, intranasally or by contact. Postmortem findings of the non-vaccinated and vaccinated chickens that died from the challenge were recorded.